Advancing Local Potential by Developing a Digital Marketing and Digital Personal Branding Application for Local Economic Growth Through Bamboo-Based Innovation - Rosmala, Dewi; Irwan, Yusril; Ungkawa, Uung; Anwar, Mochamad Hafied Ibni; Faritsi, Muhammad Hafizh Al; Fadilah, Faisal; Izzati, Sarah Nurul; Nugraha, Fazry Javier; Gunawan, M. Indra; Adhliana, Fadhli; Ramadhan, Dwi Hendra (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
This personal branding and digital marketing application was developed to address the challenge of promoting bamboo-based products and increasing market visibility for PT. Bintang Mitra Kencana. The company faced difficulties in building a strong market identity and reaching a wider audience. To address these challenges, the application emphasizes the benefits of bamboo products, the company’s commitment to sustainability, and the distinctiveness of its raw materials. Through interactive features such as a product catalog and direct purchasing options, users can easily explore, select, and purchase products. By enhancing user engagement through an intuitive digital experience, this solution supports PT. Bintang Mitra Kencana in increasing brand awareness and significantly expanding its market reach. In the long term, this digital initiative is expected to drive consistent sales growth and positively contribute to the local economy by creating greater demand for eco-friendly bamboo products.